Hilangnya Sendi Demokrasi Dan Otonomi Daerah Melalui Korporatokrasi RUU Omnibus Law - Adithya Tri Firmansyah; Ema Sarila Sinaga; Fenia Aurully Aisyah (Widya Yuridika, 2020)
One of the factors hampering the improvement of the investment climate in Indonesia is due to regulatory issues. The government is making various efforts in manifesting people's welfare, as per the Pancasila paradigm. The government is trying to increase economic growth through investment. In its implementation, the government envisages a Draft Omnibus Law that, with reasons for cutting and simplifying various regulations which are considered to be too numerous and overlapping, there are 8,451 regulations at the central level and 15,985 regional regulations. Where it makes the government confined and limited space so that the speed of government in making decisions becomes too late and not right. For the Government Omnibus law has a goal to encourage national economic growth. But there was a polemic in the process of forming this Omnibus Law Bill. Various rejection of various elements, especially the community. The Omnibus Law Bill that is in the spotlight is the work copyrights then the environment and also the principle of regional autonomy that is trying to be disturbed. The problem point of this Omnibus Law product is that it does not reflect community participation.